Carbon dot-assisted hydrothermal synthesis of flower-like MoS2 nanospheres constructed by few-layered multiphase MoS2 nanosheets for supercapacitors. Issue 81 (16th August 2016) - Wu, Jinzhu; Dai, Jun; Shao, Yanbin; Cao, Meiqi; Wu, Xiaohong
Abstract : Molybdenum disulfide (MoS2 ) has emerged as a promising electrode material for supercapacitors. Abstract : Molybdenum disulfide (MoS2 ) has emerged as a promising electrode material for supercapacitors. Elaboration of MoS2 with desired structures, morphologies and compositions as well as fabrication of MoS2 -based hybrids are current research directions. Herein, we demonstrate engineering MoS2 with a multiphase structure including 2H and 1T phases as well as edge-rich nanospherical morphology via a hydrothermal route with the assistance of carbon dots (CDs) for the first time. The resultant MoS2 3D nanospheres are formed through the self-assembly of MoS2 2D nanosheets consisting of a few atomic layers stacked along the (002) direction with an enlarged interlayer spacing. The introduced CDs not only involve the growth of the few-layered multiphase MoS2 nanosheets but also mediate the formation of MoS2 nanospheres, whilst the residual CDs may intersperse onto the surfaces of MoS2 nanospheres. The novel MoS2 nanospheres-based electrode exhibits favorable electrochemical responses in an aqueous electrolyte, such as high specific capacitance (145 F g −1 ), good rate capability and excellent cyclic stability (90% capacity retention after 2000 cycles) owing to enhanced ionic intercalation and improved electrical conductivity associated with the specific structures and morphologies. This work would pave a new pathway through the structural, morphological and compositional design for improving the electrochemical properties of transition metal dichalcogenides (TMDs) applicable as alternative energy storage materials.